(untitled) (The Research of Medical Science Review, 2025)
Introduction: Polio remains a critical public health challenge in Pakistan and Afghanistan, the last two countries where wild poliovirus (WPV) persists. Despite the Global Polio Eradication Initiative's (GPEI) substantial investments and decades-long efforts, these nations face unique socio-political and operational challenges. This study examines the persistent barriers to polio eradication, including governance issues, vaccine misinformation, and cross-border virus transmission. Objectives: The primary objective of this study is to analyze and compare the barriers to polio eradication in Pakistan and Afghanistan. It aims to highlight the impact of political instability, financial mismanagement, and operational challenges while offering policy recommendations for effective intervention strategies. Results: The findings reveal that polio eradication efforts in Pakistan and Afghanistan are severely hindered by a combination of political, social, and logistical challenges. In Pakistan, Khyber Pakhtunkhwa remains the epicenter of polio cases, accounting for 63% of the national cases in 2019. Similarly, Southern and Eastern Afghanistan continue to facepersistent outbreaks, reporting 22 cases in 2024, largely due to ongoing conflict and restricted access. Over 3.5 million children in Afghanistan remain unvaccinated due to security threats and the Taliban’s prohibition of door-to-door campaigns, while in Pakistan, extremist groups like Tehrik-i-Taliban Pakistan (TTP) propagate misinformation, increasing vaccine hesitancy. Mismanagement of international funds further exacerbates the issue, weakening vaccination programs despite the GPEI's 4.8 billion investment for 2022-2026. Additionally, the open border between the two countries facilitates cross-border virus transmission, allowing unvaccinated migrant populations to sustain outbreaks. Operational barriers, including targeted attacks on health workers in Pakistan and restricted movement in Afghanistan, further disrupt immunization drives, leaving large sections of the population unprotected. Addressing these intertwined challenges requires a multifaceted approach that emphasizes financial transparency, crossborder cooperation, and community engagement to overcome the final barriers to a polio-free future. Discussion: Polio eradication in both countries requires addressing the intertwined issues of governance, misinformation, and operational inefficiencies. Without improved financial transparency, cross-border collaboration, and community engagement, eradication efforts will remain incomplete. Conclusion: Achieving polio eradication in Pakistan and Afghanistan demands a comprehensive, multi-sectoral approach. Strengthening regional cooperation, ensuring transparency, and fostering community trust are vital steps toward eliminating the last pockets of poliovirus transmission.